Corruption Loops in Indonesia During 2004-2019 (The Need for Protection Whistleblower) - Muhadam Labolo; Juliati Prihatini; Siti Zulaika (International Journal of Applied Business and International Management, 2023)
In Indonesia, corruption occurs in all state institutions, including the executive, legislative and judiciary. The division of powers that are expected to carry out their respective functions is actually used as mutually reinforcing to commit corruption. The purpose of this study is to analyze how big the corruption loophole is in Indonesia. The method used in this study uses a literature study approach from various references. The results of the study show that although various efforts have been made by the government to eradicate corruption, corruption is still rampant. The data shows that the five highest ranks of corruption by profession/position are Private with 287, Member of DPR & DPRD 257, Echelon I/II/III 213, Other 141 and Major/Regent and Deputy 115. Plus the lack of role models at the top makes employees lower levels are also entangled in the vortex of corruption. There are many loopholes for corruption in Indonesia, protection for the role of whistleblowers and proper handling are needed to create a deterrent effect for corruptors. The imposition of severe sanctions for corruptors is only life imprisonment or death penalty, so that those concerned cannot nominate again as regional heads, members of the DPR/DPRD/DPD, President and Vice President.Keywords: Corruption, Sanctions, Governance, Preventive Measures, Whistleblower